(untitled) (Clinics, 2007)
The aims of the present work were the evaluation of allergic disease prevalence among 6 and 7 year-old students from the western districts of São Paulo city and the comparison of these data with those obtained in the International Study of Asthma and Allergies in Childhood (ISAAC) phase I, performed in the central-southern districts of São Paulo, using the ISAAC standardized written questionnaire. METHODS: 5,040 questionnaires were distributed and 3,312 were returned. Proportional differences were estimated by Chi square or Fisher exact tests. Odds Ratio and 95% confidence intervals between genders and allergic diseases were calculated. Values of p